Affiliate marketing for dummies - Mladjenovic, Paul (Tantor Media, 2020)
Get Your Piece of the Hottest Business Online Today! Affiliate marketing is your route to earning some serious bucks. Thousands of companies both large and small like Amazon, Sears, Best Buy, Overstock, Lowe's, Priceline, and others have programs so you can profit from the thousands of products they offer. Affiliate marketing is ideal for bloggers looking to monetize their work. This is a multibillion-dollar market, and there are over 10 million people involved in the biz worldwide. There's always room for more because the opportunity keeps growing as more and more companies offer affiliate programs. Affiliate Marketing For Dummies tells you how to get a slice of the pie! #9679 Choose the right affiliate product or service for you #9679 Find the best affiliate programs for you #9679 Find the best affiliate marketing strategies.